TECHNIQUES AND METHODS FOR MOTIVATION OF EMPLOYEES - Stamevska, Elizabeta (International Scientific Journal Vision, 2021)
One of the biggest problems that employers face today is employee motivation. Highly engaged employees are more motivated to be proactive and achieve their goals, enabling the organization to increase productivity. Individual or employees could be motivated through the rewards, leadership, incentives etc. Motivation in any organization is concerned with actions that should be taken to improve and sustain the level of performance of workforce or employees. Many managers struggle to keep employees motivated and engaged in the work environment because they know that motivation is one of the key factors for a company's success. The issue of employee motivation and forms of motivation is directly related to the need to provide the so-called moral and material satisfaction in the work. The synergy of these two components shapes and represents the business and managerial relationship, in its essence.